Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

This seems intuitively obvious to me, yet I can't seem to convince myself algebraically that it is.

Let $B,C>0$

Given $P(X)=P(B>C)$

Is it true that $P(X) \leq P(B \geq C)$ ? If so, what is the easiest was to demonstrate it ?

PS this is not homework.

share|cite|improve this question
up vote 3 down vote accepted

Yes, it is: $P(B\geq C) = P(B>C)+P(B = C) = P(X)+P(B=C)\geq P(X)$.

share|cite|improve this answer
Thanks. So simple ! – Joe King May 29 '12 at 11:23

I would add that the sum can be taken because the events (B>C} and {B=C} are mutually exclusive. Also it is implicit that B and C are random variables that are positive. If they were constants then P(B>=C) is either 0 or 1. If it is 0 then P(B>C)=0. If it is 1 it could be because B=C in which case P(B=C)=1 and P(B>C)=0 or B>C in which case P(B>C)=1 and P(B=C)=0. So in this trivial case P(B>=C)>=P(B>C)=P(X).

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.